Implementation Procedures for Puerto Rico's Environmental Laws - Camerón, Sara Enid (2016)
In 2004, Puerto Rico's new environmental legislation became part of the penal code with the intention of protecting the island nation's natural resources through criminal prosecution. However, the problem is a dearth of information about the prosecutions of environmental crimes and the law enforcement agent's implementation practices. The purpose of this study was to describe the execution of the law and the few cases prosecuted. Lipsky and Hull and Hjern's theory of implementation were used to help answer the research question: What are the implementation procedures of law enforcement agents on Puerto Rico's environmental crimes law, and what can be done to improve these practices? This qualitative case study included semistructured interviews with police officers and 3 district attorneys who were selected based on their involvement in environmental crimes cases. Document analysis such as court files were analyzed to reveal the implementation practices of the law. Data were analyzed using NVivo software. Results revealed that police officers and prosecutors possess little knowledge of the environmental crimes and this was not a barrier for execution of the law. However, court judges did not uniformly interpret the meaning of the law in the adjudication process which suggests that failure to successfully prosecute is due to lack of understanding of these environmental crimes by legal counsel. Enhancing the training of police, prosecutors, and judges is needed to improve policing and implementation of the law. Successful implementation practices can promote better legislation and prosecution in order to reduce environmental degradation of the island